1991
DOI: 10.1111/j.1600-051x.1991.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal condition of pregnant women assessed by CPITN

Abstract: The periodontal conditions of 2424 pregnant and 1565 non-pregnant women were assessed according to the community periodontal index of treatment needs (CPITN). The aim of this survey was to obtain information which is necessary for the planning of preventive programs of periodontal disease for pregnant women. 95% of the pregnant women and 96% of the non-pregnant women had some signs of periodontal disease. The % of pregnant women having 4 or 5 mm pockets was significantly higher than that of non-pregnant women,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
75
5
8

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 7 publications
13
75
5
8
Order By: Relevance
“…(13,14) A higher incidence of periodontitis has been seen in pregnant women than in those who were not pregnant; this incidence was found to progressively increase from the first trimester through to the third. (7,15) A probable reason for this increase could be due to the increased predisposition of periodontal tissues with increasing hormonal levels towards the end of the third trimester. (16) Changes in salivary pH were in contrast to all the examined parameters in the present study (oral hygiene, dental caries, gingival health and periodontal health).…”
Section: Discussionmentioning
confidence: 99%
“…(13,14) A higher incidence of periodontitis has been seen in pregnant women than in those who were not pregnant; this incidence was found to progressively increase from the first trimester through to the third. (7,15) A probable reason for this increase could be due to the increased predisposition of periodontal tissues with increasing hormonal levels towards the end of the third trimester. (16) Changes in salivary pH were in contrast to all the examined parameters in the present study (oral hygiene, dental caries, gingival health and periodontal health).…”
Section: Discussionmentioning
confidence: 99%
“…Although changes in periodontal status during pregnancy have been reported, the exact sequence of events from periodontal health to disease in pregnant women remains unknown. 1,2,3,4,5,6 Several factors have been investigated during research on periodontal disease in pregnancy, including hormone levels, 7,8 virulence factors of microorganisms, 9,10 changes in immunologic responses, 5,11 and microbiota. 12,13,14,15,16,17,18 Various types of analysis and models have proven helpful in understanding the multi-factorial causes of periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…12,13,14,15,16,17,18 Various types of analysis and models have proven helpful in understanding the multi-factorial causes of periodontal disease. 7,8,19,20,21 Of these, bacterial challenge studies have provided a valuable contribution to understanding the complex pathogenesis of periodontal disease. 22 …”
Section: Introductionmentioning
confidence: 99%
“…The mean number of teeth present was 28 (sd 2) per subject, mean percentage of sites with plaque present was 60.5% (sd 22.6), mean pocket depth was P regnant women demonstrate an increased level of gingival inflammation compared to non-pregnant controls. [1][2][3][4][5][6][7] There have also been studies that have shown an increased probing depth during pregnancy 1,4 however others have failed to demonstrate this finding. 3,5 A fairly consistent observation is that these changes occur in the absence of changes in oral hygiene indices.…”
mentioning
confidence: 99%